2009
DOI: 10.1038/sj.bjc.6605093
|View full text |Cite|
|
Sign up to set email alerts
|

Inhibition of the aquaporin 3 water channel increases the sensitivity of prostate cancer cells to cryotherapy

Abstract: Aquaporins (AQPs) are intrinsic membrane proteins that facilitate selective water and small solute movement across the plasma membrane. In this study, we investigate the role of inhibiting AQPs in sensitising prostate cancer cells to cryotherapy. PC-3 and DU145 prostate cancer cells were cooled to 0, À5 and À101C. The expression of AQP3 in response to freezing was determined using realtime quantitative polymerase chain reaction (RT -qPCR) and western blot analysis. Aquaporins were inhibited using mercuric chlo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
40
0

Year Published

2012
2012
2022
2022

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 44 publications
(44 citation statements)
references
References 26 publications
3
40
0
Order By: Relevance
“…Xu and associates investigated the effect of AQP3 on matrix metalloproteinase in human gastric carcinoma cells and concluded that AQP3 may be a promising drug target [29]. In the field of urological neoplasms, Ismail et al provided evidence that prostate cancer cell lines in vitro become more sensitive to cryotherapy after inhibiting AQP3 by mercuric chloride and AQP3 siRNA [30]. …”
Section: Discussionmentioning
confidence: 99%
“…Xu and associates investigated the effect of AQP3 on matrix metalloproteinase in human gastric carcinoma cells and concluded that AQP3 may be a promising drug target [29]. In the field of urological neoplasms, Ismail et al provided evidence that prostate cancer cell lines in vitro become more sensitive to cryotherapy after inhibiting AQP3 by mercuric chloride and AQP3 siRNA [30]. …”
Section: Discussionmentioning
confidence: 99%
“…Recently, it has been shown that AQP3 expression might be related to development of several carcinomas including gastric carcinoma [26,27], oesophageal and oral squamous cell carcinoma [28], cervical carcinoma [29] and cancers of the thyroid [30], pancreas [31], prostate [32,33], ovary [34] and skin [35,36]. In our study, AQP3 expression was observed in all tissue samples examined in LMS group except in one case.…”
Section: Resultsmentioning
confidence: 51%
“…AQP3 was further shown to facilitate growth of human esophageal and oral squamous cell carcinoma (Kusayama et al, 2011). In this context, downregulation of AQP3 by siRNA increased the therapeutic effect of cisplatin and led to higher sensitivity of prostate cancer cells to experimental cryotherapy (Ismail et al, 2009). …”
Section: Accepted Manuscriptmentioning
confidence: 98%